Pemberdayaan Masyarakat di Desa Kanandede Kecamatan Rongkong Kabupaten Luwu-Utara Melalui Implementasi Kebijakan Pemerintah Desa - Wijaya, Sakral (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Village government policy is a legal product because every village government has this authority. The purpose of this research is to find out the Village Government Policy in Improving Community Empowerment in Kanandede Village, Rongkong District, North Luwu Regency and what are the supporting and inhibiting factors.The method used in this study was qualitative, using data collection techniques namely observation, interviews and documentation. Based on the results of field research, it was obtained that the village government's policy in increasing community empowerment in Kanandede Village, Rongkong District, North Luwu Regency was not optimal because it can be seen from several empowerment programs which have not been realized. Then the facilities and infrastructure provided by the village government are still far from the expectations of the community. In addition, there is also the factor of a lack of community involvement in village development and empowerment because the community is more concerned with their respective activities.